2019
DOI: 10.1002/jso.25397
|View full text |Cite
|
Sign up to set email alerts
|

The application of keystone flap combined with vacuum‐assisted closure in the repair of sacrococcygeal skin defect after tumor resection

Abstract: Objective We aimed to explore the efficacy of keystone flap combined with vacuum‐assisted closure (VAC) in the repair of sacrococcygeal wounds. Methods This study is a retrospective review of patients undergoing keystone flap reconstruction between January 2014 and January 2018. A standardized data collection template was used to collect related variables. The detailed process of the reconstructive surgery is carefully described in this study. The postoperative healing process was closely observed. Results Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The resection of sacrococcygeal tumors often results in complex defects 14 ; the reconstruction of these defects is often challenging, especially when the skin defect and dead space are at different sites and when the defects are associated with exposed prosthesis and infection 15 . A previous systematic review and meta-analysis identified gluteal-based and vertical rectus abdominis musculocutaneous flaps as the 2 most common options for soft tissue reconstruction after sacrectomy 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The resection of sacrococcygeal tumors often results in complex defects 14 ; the reconstruction of these defects is often challenging, especially when the skin defect and dead space are at different sites and when the defects are associated with exposed prosthesis and infection 15 . A previous systematic review and meta-analysis identified gluteal-based and vertical rectus abdominis musculocutaneous flaps as the 2 most common options for soft tissue reconstruction after sacrectomy 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the modified Limberg flap with the pedicle at the upper pole provides thicker tissue because the blood supply to the sacrococcygeal region is more abundant here than at the lower pole. 20 Similarly, placing the flap pedicle on the upper pole minimizes the effect of flap transposition on the ipsilateral hip shape, resulting in better surgical aesthetic results. It should be noted that the side length of the flap was calculated based on the distance between the intersection point and the lower pole.…”
Section: Discussionmentioning
confidence: 99%
“…The keystone flap has been reported to be a versatile flap for reconstruction of the head and neck, 11 trunk, 12 limb, 13 and perineal regions. 12 It can be used as a primary or secondary reconstructive option, and it can be performed simultaneously with another flap.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a successful reconstruction, a proper debridement of devitalized tissue and, in some occasions, an application of a vacuumassisted closure device, may be required. 13 The intrinsic elasticity of the keystone flap allows for a reduction and a redistribution of the tension compared to the pre-flap wound. 5,14 The wound is designed in an elliptical shape, with one after tumor resection, epidermoid cyst removal, or treatment of myelomeningoceles.…”
Section: Discussionmentioning
confidence: 99%